2011
DOI: 10.4028/www.scientific.net/amr.383-390.3140
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Of the Epoxy Resin of the Waste Printed Circuit Boards Using Solvent Extraction

Abstract: Currently, the number of the waste printed circuit boards (WPCB) is increasing. The technologies of extracting and reclaiming of the value of the metallic fraction of WPCB have been used widely because of the major economic driving force. But the non-metallic fractions (NMFs), which take up almost 70wt% of waste WPCB, were mainly treated by combustion or land filling in the past. However, combustion of the NMFs will cause the formation of highly toxic polybrominated dibenzodioxins and dibenxofurans (PBDD/Fs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Indeed, numerous studies have been reported in the area of nitric acid decomposition, such as in the cases of CFRPs 29,30 and waste printed circuit boards. 31,32 In addition, applications of the decomposed resin from aminecured epoxy resins as an oil absorption material have been reported, 33,34 and our group has also reported the applications as a catalyst for acid-anhydride-cured epoxy resins. 35,36 Thus, we herein report the creation of a closed loop of materials by utilizing resins decomposed in nitric acid as an amine curing agent.…”
Section: ■ Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, numerous studies have been reported in the area of nitric acid decomposition, such as in the cases of CFRPs 29,30 and waste printed circuit boards. 31,32 In addition, applications of the decomposed resin from aminecured epoxy resins as an oil absorption material have been reported, 33,34 and our group has also reported the applications as a catalyst for acid-anhydride-cured epoxy resins. 35,36 Thus, we herein report the creation of a closed loop of materials by utilizing resins decomposed in nitric acid as an amine curing agent.…”
Section: ■ Introductionmentioning
confidence: 87%
“…In this study, we focused on the nitric acid decomposition of amine-cured epoxy resins. Indeed, numerous studies have been reported in the area of nitric acid decomposition, such as in the cases of CFRPs , and waste printed circuit boards. , In addition, applications of the decomposed resin from amine-cured epoxy resins as an oil absorption material have been reported, , and our group has also reported the applications as a catalyst for acid-anhydride-cured epoxy resins. , …”
Section: Introductionmentioning
confidence: 89%
“…It consists of first dissolving or decomposing their epoxy resins constituents. Early reports proposed to use concentrated nitric acid (8 N) at 80 • C for 3h, but yields were small [69,70]. Zhu et al, proposed to use Dimethyl Sulfoxide (DMSO) instead [39,71].…”
Section: Dismantling Via Epoxy Resin Treatmentmentioning
confidence: 99%
“…Various separation processes of metal and nonmetallic ingredients of MWPCBs viz. physical recycling processes (e.g., shredding, hammer milling, ball milling, corona discharge separation, magnetic separation, eddy current separation, air classification, flotation, gravity separation, and density-based separation), thermal processing (pyrolysis, gasification, and plasma treatment), hydrometallurgical processing, , and solvent extraction (dimethyl sulfoxide, dimethyl formamide, N -dimethyl pyrrolidone, and ionic liquids) had been reported in last few decades. In recent years, hydrometallurgical processes attracted particular attention for the treatment of WPCBs.…”
Section: Introductionmentioning
confidence: 99%